Characterizing caspase-1 involvement during esophageal disease progression. - Creagh, Emma; O'Sullivan, Jacintha; Reynolds, John; Ravi, Narayanasamy; Phelan, James (My University, 2020)
Barrett’s esophagus (BE) is an inflammatory condition and a neoplastic precursor to esophageal adenocarcinoma (EAC). Inflammasome signaling, which contributes to acute and chronic inflammation, results in caspase-1 activation leading to the secretion of IL-1β and IL-18, and inflammatory cell death (pyroptosis). This study aimed to characterize caspase-1 expression, and its functional importance, during disease progression to BE and EAC. Three models of disease progression (Normal–BE–EAC) were employed to profile caspase-1 expression: (1) a human esophageal cell line model; (2) a murine model of BE; and (3) resected tissue from BE-associated EAC patients. BE patient biopsies and murine BE organoids were cultured ex vivo in the presence of a caspase-1 inhibitor, to determine the importance of caspase-1 for inflammatory cytokine and chemokine secretion. Epithelial caspase-1 expression levels were significantly enhanced in BE (p < 0.01). In contrast, stromal caspase-1 levels correlated with histological inflammation scores during disease progression (p < 0.05). Elevated secretion of IL-1β from BE explanted tissue, compared to adjacent normal tissue (p < 0.01), confirmed enhanced activity of caspase-1 in BE tissue. Caspase-1 inhibition in LPS-stimulated murine BE organoids caused a significant reduction in IL-1β (p < 0.01) and CXCL1 (p < 0.05) secretion, confirming the importance of caspase-1 in the production of cytokines and chemokines associated with disease progression from BE to EAC. Targeting caspase-1 activity in BE patients should therefore be tested as a novel strategy to prevent inflammatory complications associated with disease progression.
PUBLISHED
Keywords: Esophageal cancer; Inflammation; Barrett’s metaplasia; Inflammasome; Cancer; Immunology, Inflammation & Infection; BARRETTS ESOPHAGUS; Inflammasome-mediated inflammation; Oesophageal Cancer; caspase-1; Chronic Health Condition; Health